PENGARUH LATIHAN CONE DRILL TERHADAP KELINCAHAN ATLET CLUB BOLA VOLI PUTRA JUNIOR SWADAYA PEKANBARU - Depita Sari; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study was obtained during sparring and training, namely the athlete had difficulty reaching the ball that would fall far from his standing position and could not change direction quickly when performing several techniques such as defense and bloc so that the opponent could generate points easily. The purpose of the study was to see the effect of cone drill exercises on agility. This type of research was an experiment to see the effect of the form of exercise. The population in this study was the athletes of the junior men's volleyball club, Swadaya Pekanbaru, which amounted to 11 people. The sampling technique is total sampling, in which the total population is sampled. The data collection method was carried out with two tests, namely an initial test (pree-test) before doing the cone drill exercise and a final test (post-test) after doing the cone drill exercise, for 16 meetings three times a week with a total sample of 11 people. The instrument in this study used agility t-test. The analysis was carried out using a t-test, based on the t-test analysis yielded Tcount > Ttable. The results of the hypothesis test showed that there was a significant effect of cone drill (X) training on the agility (Y) of the junior male volleyball club athlete of Swadaya Pekanbaru.Key Words: Practice Cone Drill, Agility, Volleyball